Antimicrobial preservation efficacy of liquid glucose and liquid maltitol syrups with and without 0.1% sorbic acid - Carpentier Thomas; Maillard Eve; Royer Mathilde; Mustapha Lina; Marçon Frédéric (De Gruyter, 2021)
Amongst paediatric pharmaceutical forms, syrups offer advantages such as ease of administration and good palatability. They also exhibited microbial self-preservation properties that may be useful to enhance shelf life of liquid formulation. The objective of our works is to test the self-preservation efficacy of maltitol and glucose syrup without or with sorbic acid as described in the European pharmacopoeia.